Population Suppression Strategy Through Balanced Family Planning Counseling on the Decision to Select Postpartum Family Planning - Rahmadiyanti; Octafian, Ade Citra; Purnama, Dian; Elistari; Saragih, H. Rodearny; Susilowati, Hanifah; Hairani, Irma; Beninda, Jihan Afifah (Postgraduate, University of Mataram, 2024)
The Balanced Counseling Strategy for Family Planning (SKB-KB) significantly influences the decision to choose Postpartum Family Planning (KBPP). SKB-KB provides comprehensive information to couples about contraceptive methods after childbirth. This study aims to assess the impact of SKB-KB counseling on KBPP decisions in 2024 and its contribution to population reduction. A quasi-experimental method was used, with sample size determined by G-Power software, involving 71 respondents aged 38-39 weeks, divided across seven healthcare facilities. These include TPMB Alfiatun Jannah Asmin Jakarta, UPTD Sobang Public Health Center, Cipanas Inpatient Health Center, and others. The study employed a one-group pre-test and post-test design to measure the impact of counseling. Results show that SKB-KB counseling significantly affects the choice of postpartum contraception, indicating its potential in reducing population growth. The findings highlight that midwives can effectively educate family planning acceptors using balanced counseling strategies, helping them make informed contraceptive choices. This strategy is essential in contributing to population control efforts.